Analysis of 500kV composite insulator fracture fault. (September 2020) - Liu, Hui; Yang, Tianshu; Zhou, Chao; Jia, Ran; Zhang, Yang; Qi, Zhao
Abstract: This paper describes the fracture of composite insulator string of B phase on Tower 72 of 500kV line. A series of tests have been taken on the core rod and sheath to analyze the causation of the accident, including hydrophobicity test, dissection analysis, dye penetration, SEM and FTIR. It is found that the surface of the fault insulator is chalked, and its hydrophobicity is reduced. The interface between the epoxy resin matrix and silicone rubber sheath has completely failed. Epoxy resin matrix has been degraded, and partial discharge on the surface of core rod accelerates this process. The main chain of Si-O and side chain of Si-C in silicone rubber molecule are severely broken, and the surface of the umbrella is aging. It is concluded that the interface failure between sheath and core rod is the main cause of crisp fracture. Partial discharge at high voltage end and weak interface between glass fiber and epoxy resin matrix result in the development of degradation channels. Pollution and chalking on the surface of umbrella also explain part of the reason.